Computer Models in Dynamic Economics - Cohen, Kalman J.; Cyert, Richard M. (Quarterly Journal of Economics, 1961)
Introduction, 112. — Theory construction (model building), 113. — General characteristics of computer models, 115. — Comparison of computer models with operations research simulations and econometric models, 117. — Methodological problems of computer models, 119. — Review of the literature, 121. — Future of computer models, 126.